Determination of heavy metals content in agriculture products in regions suffered from hostilities: first results (Environment & Health, 2025)
The purpose of the work - determination of heavy metals concentrations in grain and vegetable crops (wheat, vegetables) grown in areas affected by hostilities.The aim of the work - to determine the concentrations of heavy metals in grain and vegetable crops (wheat, vegetables and greens) grown in areas affected by hostilities.Materials and methods. The research was carried out in areas affected by hostilities. The content of lead, cadmium, copper and zinc in the samples was determined by the method of inversion voltammetry using the analyzer "АВА-1-01".Conclusions. Increased levels of heavy metal contamination of agricultural products in war-affected regions have been identified, exceeding permissible standards in 7–10% of cases. This poses a potential threat to public health and requires further monitoring, food safety control, and implementation of risk reduction measures.
Keywords: military operations; heavy metals; grain; vegetables; food security